The Aortic Pathologies: How Far We Understand It and Its Implications on Thoracic Aortic Surgery - Harky,Amer (2021)
Abstract Thoracic aortic diseases contribute to a major part of cardiac surgeries. The severity of pathologies varies significantly from emergency and life-threatening to conservatively managed conditions. Life-threatening conditions include type A aortic dissection and rupture. Aortic aneurysm is an example of a conservatively managed condition. Pathologies that affect the arterial wall can have a profound impact on the presentation of such cases. Several risk factors have been identified that increase the risk of emergency presentations such as connective tissue disease, hypertension, and vasculitis. The understanding of aortic pathologies is essential to improve management and clinical outcomes.